2017
DOI: 10.3389/fnins.2017.00482
|View full text |Cite
|
Sign up to set email alerts
|

Deceptive but Not Honest Manipulative Actions Are Associated with Increased Interaction between Middle and Inferior Frontal gyri

Abstract: The prefrontal cortex is believed to be responsible for execution of deceptive behavior and its involvement is associated with greater cognitive efforts. It is also generally assumed that deception is associated with the inhibition of default honest actions. However, the precise neurophysiological mechanisms underlying this process remain largely unknown. The present study was aimed to use functional magnetic resonance imaging to reveal the underlying functional integration within the prefrontal cortex during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 79 publications
(136 reference statements)
0
12
0
1
Order By: Relevance
“…The TOM network is considered to be associated with inferring thoughts and beliefs of other people [43][44][45][46][47] . Additionally, PPI analysis in the fMRI study, with a similar game design in which participants performed deceptive and manipulative honest claims according to free choice with the aim of defeating an opponent, revealed the involvement of this brain area 19 . During both manipulative actions, regardless of their truthfulness, the rTPJ was involved in interaction with the left middle frontal gyrus (lMFG), and no significant difference in functional interactions between the rTPJ and lMFG was observed when comparing deceptive and truthful conditions.…”
Section: Neural Mechanisms Of Deception In a Social Context: An Fmri mentioning
confidence: 96%
See 2 more Smart Citations
“…The TOM network is considered to be associated with inferring thoughts and beliefs of other people [43][44][45][46][47] . Additionally, PPI analysis in the fMRI study, with a similar game design in which participants performed deceptive and manipulative honest claims according to free choice with the aim of defeating an opponent, revealed the involvement of this brain area 19 . During both manipulative actions, regardless of their truthfulness, the rTPJ was involved in interaction with the left middle frontal gyrus (lMFG), and no significant difference in functional interactions between the rTPJ and lMFG was observed when comparing deceptive and truthful conditions.…”
Section: Neural Mechanisms Of Deception In a Social Context: An Fmri mentioning
confidence: 96%
“…In neuroimaging studies, the bilateral TPJ was reported to be associated with the judgement of deception 55,56 . However, only the rTPJ was demonstrated to increase activity during deception 3,19,30,48,49 . Therefore, the current results confirm the involvement of socio-cognitive processes in deception and expand the existing fMRI data, demonstrating that BOLD signal increases in both the right and left TPJ during the execution of deception.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…Similar results have been obtained in a related research field, i.e., deception/dishonest behavior. A consistent finding of studies in this field ( Priori et al, 2008 ; Greene and Paxton, 2010 ; Kireev et al, 2017 ; Sun et al, 2017 , for a review see Abe, 2011 ) is that the deceptive act goes along with increased activation of brain regions involved in conflict detection and resolution, as the ACC and DLPFC. Interestingly, some brain studies have also provided evidence for the opposite pattern (e.g., Zhu et al, 2014 ; Maréchal et al, 2017 ).…”
Section: Discussionmentioning
confidence: 55%
“…Studies on the neural basis of deception have important theoretical and clinical implications [1, 2]. Abundant evidence from neuroimaging has revealed how the brain processes deception [3, 4]. Most studies support the hypothesis that greater cognitive control and conflict suppression (i.e., the inhibition of honest reaction) are required during deception [5, 6].…”
Section: Introductionmentioning
confidence: 99%